2009
DOI: 10.1111/j.1365-313x.2009.03919.x
|View full text |Cite
|
Sign up to set email alerts
|

Defect in non‐yellow coloring 3, an α/β hydrolase‐fold family protein, causes a stay‐green phenotype during leaf senescence in rice

Abstract: SUMMARYChlorophyll degradation is an important phenomenon in the senescence process. It is necessary for the degradation of certain chlorophyll-protein complexes and thylakoid membranes during leaf senescence. Mutants retaining greenness during leaf senescence are known as 'stay-green' mutants. Non-functional type stay-green mutants, which possess defects in chlorophyll degradation, retain greenness but not leaf functionality during senescence. Here, we report a new stay-green mutant in rice, nyc3. nyc3 retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
154
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(172 citation statements)
references
References 48 publications
10
154
0
2
Order By: Relevance
“…In addition increasing H 2 O 2 induced by oxidative stress increase the photo-oxidation of photosystem antennae under salinity stress (Yamazaki et al, 2003 andKafi, 2009). The reduction of Chl.a and Chl.b may be due to an increase of chlorophyllase enzyme which converts chlorophyll into chlorophyllide and phytol (Morita et al, 2009 andLin et al, 2016) and/or damaging of photosynthetic apparatus through block of pigment-protein complexes (proteins of PSII) which synthesized in the chloroplasts (Nishiyama et al, 2011). More or less similar results were reported by Hidri et al (2016).…”
Section: Photosynthetic Parameterssupporting
confidence: 73%
“…In addition increasing H 2 O 2 induced by oxidative stress increase the photo-oxidation of photosystem antennae under salinity stress (Yamazaki et al, 2003 andKafi, 2009). The reduction of Chl.a and Chl.b may be due to an increase of chlorophyllase enzyme which converts chlorophyll into chlorophyllide and phytol (Morita et al, 2009 andLin et al, 2016) and/or damaging of photosynthetic apparatus through block of pigment-protein complexes (proteins of PSII) which synthesized in the chloroplasts (Nishiyama et al, 2011). More or less similar results were reported by Hidri et al (2016).…”
Section: Photosynthetic Parameterssupporting
confidence: 73%
“…Phytol removal is important for two reasons: (1) it renders chlorophyll breakdown products water soluble (that is, a prerequisite for their ultimate storage in the vacuole as phyllobilins; Matile et al, 1988;Kräutler and Hörtensteiner, 2013); and (2) removal of phytol is regarded as a prerequisite for the degradation of chlorophyll-binding proteins during senescence. Thus, mutants that are incapable of phytol hydrolysis, such as Arabidopsis pph-1 and rice nonyellow coloring3 (nyc3), exhibit a stay-green phenotype during leaf senescence and retain large quantities of light-harvesting complex subunits (Morita et al, 2009;Schelbert et al, 2009). Likewise, mutations in Pheophytin a + b or chlorophyll a + b was used as substrate, and the formation of the respective products (pheophorbide a or chlorophyllide a) was analyzed by HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that the two CLHs of Arabidopsis are dispensable for leaf senescence . Instead, we and others identified a novel esterase, PHEOPHYTI-NASE (PPH), which specifically dephytylates pheophytin, but not chlorophyll, and is required for chlorophyll breakdown in Arabidopsis and rice (Oryza sativa; Morita et al, 2009;Schelbert et al, 2009;Ren et al, 2010). Thus, PPH-deficient mutants exhibit a stay-green phenotype, which is characterized by a high retention of chlorophyll together with the accumulation of significant amounts of pheophytin during leaf senescence.…”
mentioning
confidence: 99%
“…Consistent with this, Arabidopsis pph mutants accumulated Phein during leaf senescence (Schelbert et al 2009). Arabidopsis PPH, alternatively named CRN1 by Ren et al (2010), and its rice ortholog, termed NCY3 (Morita et al 2009), were shown to localize to the chloroplast and deficiency in respective mutants caused a stay-green phenotype. In summary, there is striking evidence that during leaf senescence, at least in Arabidopsis, dephytylation occurs after Mg removal, by the Phein-specific action of PPH.…”
Section: Mg-dechelation and Dephytylationmentioning
confidence: 99%
“…Recently three independent groups (Schelbert et al 2009;Ren et al 2010;Morita et al 2009) succeeded in identifying a candidate esterase for phytol cleavage in Arabidopsis and rice, and in one case was the recombinant Arabidopsis enzyme biochemically analyzed (Schelbert et al 2009). It exhibited esterase activity towards Pheophytin (Phein) a or Phein b, yielding the respective Pheide pigment, but did not accept Chls as substrate.…”
Section: Mg-dechelation and Dephytylationmentioning
confidence: 99%